Sleep apnea: An overlooked cause of lipotoxicity?. (October 2017) - Gu, Chenjuan; Younas, Haris; Jun, Jonathan C.
Abstract: Obstructive sleep apnea (OSA) is a common sleep disorder associated with diabetes and cardiovascular disease. However, the mechanisms by which OSA causes cardiometabolic dysfunction are not fully elucidated. OSA increases plasma free fatty acids (FFA) during sleep, reflecting excessive adipose tissue lipolysis. In animal studies, intermittent hypoxia simulating OSA also increases FFA, and the increase is attenuated by beta-adrenergic blockade. In other contexts, excessive plasma FFA can lead to ectopic fat accumulation, insulin resistance, vascular dysfunction, and dyslipidemia. Herein, we propose that OSA is a cause of excessive adipose tissue lipolysis contributing towards systemic "lipotoxicity". Since visceral and upper-body obesity contributes to OSA pathogenesis, OSA-induced lipolysis may further aggravate the consequences of this metabolically harmful state. If this hypothesis is correct, then OSA may represent a reversible risk factor for cardio-metabolic dysfunction, and this risk might be mitigated by preventing OSA-induced lipolysis during sleep.